137Caesium in samples of wild-grown Boletus edulis Bull. from Lucca province (Tuscany, Italy) and other Italian and European geographical areas. Issue 1 (2nd January 2017) - Betti, Laura; Palego, Lionella; Lucacchini, Antonio; Giannaccini, Gino
ABSTRACT: Samples of the edible mushroom Boletus edulis Bull. were studied to assess the risk for human health related to their content of the artificial radionuclide 137 Cs. Fresh B. edulis carpophores were collected in four undeveloped microhabitats of Lucca province (Tuscany, North-Central Italy). Dried non-cultivated samples coming from this same district and 11 other Italian provinces or European countries were instead purchased fromcommercial sources. Contents of 137 Cs, reported as Bq kg ‒1 dry weight (dw), were measured by γ-spectrometry. The radionuclide concentration varied depending on the gathering site in fresh samples, with 41.8 ± 5.2 Bq kg ‒1 dw at site 1 (Tosco-Emiliani Apennine) and four-fold less, 12.8 ± 1.3 Bq kg ‒1 dw, at site 2 (Apuan Alps). Moreover, fresh or dried carpophores from Lucca province displayed among the lowest 137 Cs contents in Europe. Average 137 Cs levels in all analysed samples were substantially below the legal threshold for edible mushrooms, 600 Bq kg ‒1 dw. Conclusively, we report that 137 Cs amounts in B. edulis depend on both the distance from the Chernobyl accident and multifactorial features of collection sites. We also show that the consumption of European B. edulis does not represent a major health risk with respect to 137 Cs radio contamination. GRAPHICAL ABSTRACT: